Dichotomy in the tissue origin of schistosome acquired class I and class II major histocompatibility complex antigens (The Rockefeller University Press, 1984)
Schistosoma mansoni schistosomula recovered from the lungs of mice have previously been shown to express host-derived class I and class II major histocompatibility complex (MHC) antigens. To investigate the tissue origin of parasite-acquired MHC products, lung-stage schistosomula were obtained from a series of parent leads to F1 and F1 leads to parent bone marrow chimeras and the parasites typed by immunofluorescence for the presence of haplotype-specific K region and I region MHC determinants. The results of these experiments indicated that, despite their intravascular residence in the host, schistosomula derive all of their class I antigen from a nonhemapoietic tissue source. In contrast, the class II antigens expressed on the surface of schistosomula were found to originate from bone marrow-derived donor cells. These results support the hypothesis that MHC product acquisition by schistosomes involves selective and specific interactions with host tissue and, in the case of class I antigens, suggest that the endothelium may be a major site of host molecule uptake for the parasite.